Comparison of Performance Evaluation within Public Sector Undertakings during Reform Eras: A Literature Review - Roshan Baa; Dr. A. K. Chattoraj (Revista Interdisciplinar de Ciência Aplicada, 2025)
Public sector undertakings (PSUs) were developed by the Indian government to overcome the critical issues faced post-independence. This study aims to review the understanding of PSUs in the Indian context in terms of their performance. The evolution, attributes, and significance of the Indian economy are discussed. The current status of PSUs as perceived from secondary data is described and the studies related to performance within the types of PSUs and the various time zones are comprehensively reviewed. It has been realized that even though there are few studies evaluating the performance productivity using performance indicators, studies are still lacking concerning the comparison of Maharatna, Navratna, and Miniratna companies. To fill this gap, the present review undertakes an analysis by comparing the performance of the three main PSU categories. In addition, the reasons for underperformance are also elucidated. Based on these, recommendations for enhancing performance in the Indian PSUs are suggested. This review assists in comprehending the functioning of PSUs, which intends to help and assist the Ministry of Finance, policymakers, potential investors, state governments, administrative management of the PSUs, researchers, educationists, and other stakeholders to direct the PSUs towards sustainable progress in terms of better performance efficiency.